2012
DOI: 10.1200/jco.2011.41.5919
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Brain Metastasis in a Patient With Ovarian Cancer With BRCA2 Mutation

Abstract: A 57-year-old white woman presented to an outside hospital with shortness of breath. She was noted to have bilateral pleural effusions and an intra-abdominal cystic mass on a computed tomography (CT) scan. Diagnostic thoracentesis was performed at that time. The cytology showed adenocarcinoma cells, which were consistent with metastatic spread from ovarian primary. Debulking surgery was performed at the outside hospital that consisted of a total abdominal hysterectomy with bilateral salpingooophoerectomy, appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Furthermore, Sekine et al 16 , investigating the incidence of brain metastases in BRCA1related ovarian cancers, reported that four of seven cases with brain metastases secondary to ovarian cancer were BRCA1-related. Finally, Root and Armaghany 19 reported a case of a BRCA2-positive ovarian cancer patient who developed a solitary brain metastasis 3 years after being diagnosed with papillary cystadenocarcinoma (Table 1).…”
Section: Editorialmentioning
confidence: 99%
“…Furthermore, Sekine et al 16 , investigating the incidence of brain metastases in BRCA1related ovarian cancers, reported that four of seven cases with brain metastases secondary to ovarian cancer were BRCA1-related. Finally, Root and Armaghany 19 reported a case of a BRCA2-positive ovarian cancer patient who developed a solitary brain metastasis 3 years after being diagnosed with papillary cystadenocarcinoma (Table 1).…”
Section: Editorialmentioning
confidence: 99%
“…Ovarian cancer often spreads loco-regionally in the abdomen and distant metastasis are infrequently observed (4). Amongst these abdominal diseases, brain metastases from malignancies of the female genital tract have rarely been reported, with an incidence of only 0.4–1.2% in metastatic cervical cancer patients (57), 0.3–0.9% in the majority of metastatic endometrial cancer cases (4,8) and <2% in metastatic ovarian cancer cases (9,10). Despite decades of studies on the management of brain metastases from lung, renal and gastrointestinal cancer, melanoma and other cancers, there is hardly any available literature on brain metastases from gynecological malignancies.…”
Section: Introductionmentioning
confidence: 99%